State-led bricolage and the extension of collective governance: Hybridity in the Swiss skill formation system - Lukas Graf; Alexandra Strebel; Patrick Emmenegger (Regulation & Governance, 2021)
This paper explores the extension of collective governance to sectors without collective governance tradition. We introduce the concept of state-led bricolage to analyze the expansion of the Swiss apprenticeship training system – in which employer associations fulfill core collective governance tasks – to economic sectors in which training had previously followed a school-based and state-oriented logic. In deindustrializing societies, these sectors are key for the survival of collectively governed training systems. Through a mixed-methods analysis, we examine the reform process that led to the creation of new intermediary organizations that enable collective governance in these sectors. In addition, we compare the organizational features of these organizations with the respective organizations in the traditional crafts and industry sectors. We find that the new organizations result from state-led bricolage. They are hybrid organizations that reflect some of the bricoleur's core policy goals and critically build on the combination of associational and state-oriented institutional logics.
Keywords: 330; collective governance; hybridity; industrial relation; skill formation; state-led bricolage